Hubungan Antara HbA1c Dengan LDL-K dan Albuminuria pada Penderita DM dengan Riwayat Komplikasi Jantung Koroner - Driyah, Srilaning; Rachmawati, Banundari; Asti, Herniah (Jurnal Biotek Medisiana Indonesia, 2016)
The prevalence of Diabetes Mellitus (DM) globally is elevated continually. Poor blood glucose control to diabetes patients caused both macrovascular complications (ex.coronary heart disease/CHD) andÂ  microvascular complications (ex.nephropathy). Blood glucose controlled is need to be done in every 3 months regularly using HbA1C as a diabetic parameter, regarding to the high risk mortality of the complications. Low density lipoprotein cholesterol (LDL-C) is dyslipidemia Â characteristics and LDL-C is a lipoprotein proatherogenic. Albuminuria test is also needed as an early marker of micro and macrovascular disorders, which reflects the general process of endothelial damages (vascular dysfunction).The aim of this study is to prove any relationship between HbA1C levels with LDL-C and albuminuria levels in diabetic patients with history of coronary heart complications.This study is performed an analytical observational study with cross sectional approach. Thirty diabetic patients with any history of CHD complications were enrolled, then laboratory analysis of HbA1C by ion exchange HPLC, LDL-C levels were using colorimetric enzymatic method and albuminuria test withÂ  the photometric method. Differences between variables were analyzed using by Spearman correlation-testHbA1C levels in 10 patients (33,3 %) are <7% and in 19 patients are â¥ 7% (66,7 % ). LDL-C (<100mg/dl) in 13 patients (43,3%), LDL-C (â¥100mg/dl) in 17 patients (56,7%), Normoalbuminuria (< 20 mg/L ) in 11 patients (36.7%), albuminuria (â¥20 mg/L) in 19 patients (63,3%).There is a moderate positive relationship between HbA1C and LDL-C levels (r=0.385, p=0.014) and a positive strong relationship between HbA1C and albuminuria levels (r=0.52, p=0.004).Conclusions: The higher HbA1C levels, the higher LDL-C and albuminuria levels would be.